WOMEN AGAINST WOMEN: THE SOCIOLINGUISTICS OF HAUSA PROVERBS - A. Bashir, Amina; O. Idris Amali, Halima (Proverbium - Yearbook, 2012)
Proverbs are widely known to be sayings which convey the feeling of the inner mind in some metaphoric presentations. This study discusses Hausa proverbs (in rivalry) from the feminist and sociolinguistic perspectives. Ten Hausa proverbs are presented, translated into English and analysed using sociolinguistic parameters of when, where, why and who uses the proverbs. Women in polygamous homes are rivals to one another. Their rivalry originates from the fact that they owe their loyalty to the same man. Each wife sees the other as a block to the “total” pleasure she desires from “their” husband. Even though they may have accepted the situation of sharing the man, they still find ways to express their inner feelings of pains against each other by employing the use of proverbs, which is a metaphoric way of expression, without realising they also puncture the image of the entire female gender, the image which women should all guard jealously.